Airport systems planning, design, and management - De Neufville, Richard 1939-; Odoni, Amedeo R. (McGraw-Hill, 2003)
The new standard on airport systems planning, design, and management ; Provides solutions to the most pressing airport concerns: expansion, traffic, environment, additions, etc. ; Full coverage of computer-based tools and methodology ; Additional reports and updates available via authors' website.